Natural products derived from traditional chinese medicine as novel inhibitors of the epidermal growth factor receptor - Sertel, Serkan; Plinkert, Peter K.; Efferth, Thomas (Combinatorial chemistry & high throughput screening, 2010)
The epidermal growth factor receptor (EGFR) has become an important molecular target in cancer therapy. Various small molecules and therapeutic antibodies targeting EGFR family members have been developed during recent years and are established in clinical oncology. However, increasing - clinical application of EGFR tyrosine kinase inhibitors has resulted in the development of resistance to EGFR-targeting drugs due to the selection of EGFR-mutated variants. This phenomenon forced the search for novel EGFR inhibitors with activity towards EGFR-mutant tumors. This review describes - recent achievements in natural products derived from medicinal plants as novel EGFR inhibitors.